Screening for ASD in adults with ID—moving toward a standard using the DiBAS‐R and the ACL. Issue 5 (May 2016) - Mutsaerts, C. G.; Heinrich, M.; Sterkenburg, P. S.; Sappok, T.
Abstract: Background: Identification of Autism Spectrum Disorder (ASD) in persons with intellectual disability (ID) is challenging but essential to allow adequate treatment to be given. This study examines whether the combination of two ASD screening instruments specifically developed for persons with ID, namely, the Diagnostic Behavioral Assessment for ASD—Revised (DiBAS‐R) and the Autism Checklist (ACL), improves diagnostic accuracy when used in combination compared to the application of the single instrument. Method: A clinical sample of adults with ID who are suspected of having ASD ( N =148) was assessed using two ID specific screening scales (DiBAS‐R and ACL). The diagnostic validity of the single instruments and of their combination was assessed. Results: While both instruments showed acceptable diagnostic validity when applied alone (DiBAS‐R/ACL: sensitivity: 75%/91%; specificity: 75%/75%; overall agreement: 75%/83%), specificity increased when two positive screening results were used (88%), and sensitivity increased (95%) when at least one positive screening result was used. Conclusions: Different combinations of the ASD screening instruments DiBAS‐R and ACL lead to improvements in sensitivity and specificity. The complementary use of the ACL in addition to the sole use of the DiBAS‐R improves overall accuracy.